Development of integrated STEM education learning units to access students' systems thinking abilities - Bevo Wahono; Arinal Husna; Slamet Hariyadi; Yenny Anwar; Meilinda Meilinda (Jurnal Inovasi Teknologi Pendidikan, 2023)
This research aims to develop a Biology Science learning unit based on Science, Technology, Engineering, and Mathematics (STEM) that is valid, practical and effective in accessing students' system thinking skills. The topic ,of the Biology Science learning unit is the water cycle. The development used the ADDIE model research and development for the research method. The research subjects were 32 grade VII students from State Junior High School in Jember. The research findings showed that the average validation result of STEM-based learning units was 95.3%. These can be considered valid. The Paired Sample Test result is 0.001 or less than 0.05, so there is a significant difference between the pretest and post-test results. The average effectiveness test score is 0.73, higher than the typical gain test score, and the results include the high criteria. Finally, the average percentage of practicality tests is in the high category of 89%.  System thinking skills are needed in learning activities to describe and solve a problem using integrated STEM education. Therefore, the STEM-based learning unit on the water cycle topic could be applied in the learning process to acquire students' system thinking abilities in the Biology Science learning unit. Finally, assessing student responses during the learning using this learning unit is pivotal for future research.